Pregnancy Education Can Reduce Stress and Mothers Remain Fit an Delivery During The Covid 19 Pandemic - Iceu Amira; Hendrawati Hendrawati; Sukma Senjaya; Indra Maulana (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Pain in labor can cause blood pressure to increase which causes stress and disrupted labor, this can certainly hamper labor so that the delivery time will be longer. The purpose of the activity is to increase knowledge and understanding of pregnancy exercise which can reduce stress so that delivery runs smoothly during the covid-19 pandemic. The method used is webinar via zoom, question and answer and demonstration and poster distribution. The results of the health webinar activity are named “Pregnancy Gymnastics Education Can Reduce Stress and Mothers Stay Fit During Delivery During Covid-19”. which will be held on Sunday, April 25, 2021, starting at 09.00 to 12.00. In the process of conducting the webinar; The participants looked very enthusiastic when the material was given. Participants participated in the webinar enthusiastically even though it was conducted online. The webinar activity was conducive because the participants paid attention to the material presented well and asked questions.